Analisis Kesalahan Dalam Menyelesaikan Soal Cerita Matematika Materi Aritmatika Sosial Berdasarkan Tahapan Newman Pada Siswa Kelas VII SMP Negeri 17 Mataram Tahun Pelajaran 2021/2022 - Yuliana; Laila Hayati; Muhammad Turmuzi; Nurul Hikmah (Pendidikan Matematika FKIP Universitas Mataram, 2022)
This study aims to find out the types of student’s errors of grade VII in SMPN 17 Mataram work on mathematic narrative questions, the factors that make student’s error’s to solve mathematic narrative questions and to find out the most dominant types of mistakes made by SMPN students 17 Mataram is based on Newman’s classification of errors. This research method is descriptive qualitative. Data collection was carried out using the written test method and in-depth interviews. The subjects in this study were 24 students of grade VII-C of SMPN 17 Mataram. The results shows the percentage of errors made by students in solving mathematic questions related to social aritmetic material based on Newman’s procedures were: (a) the percentage of errors in reading made by students was 22,22%, (b) the percentage of errors in understanding the problem was 26,45%, (c) the percentage of errors intransformation was 52,91%, (d) the percentage of errors in processing skill was 54,49%, (e) the percentage of errors in writing the final answer was 42,85%. The factor that cause students’ mistakes are not reading the questions carefully, improperly in finding out what is known in the quation, lacking the core problem inside the question, confusing the formula should be used and following friends’ answer